Infinitesimal etendue and Simultaneous Multiple Surface (SMS) concentrators for fixed receiver troughs - Canavarro, Diogo; Collares-Pereira, Manuel; Chaves, Julio (Solar Energy, Elsevier, 2013)
In order to increase the cost-effectiveness of conventional parabolic trough (PT) fields it is essential to reduce Capital Expenditure (Capex) as well as Operations and Maintenance (O&M) costs, in particular the need for flexible hosing or rotating joints, which are used because the tubular receiver also tracks in a solidary way with the trough. One possible alternative is to design a different type of optic with the center of mass on the center of the tubular receiver, generating the possibility of it being fixed, thereby dispensing with flexible hosing or rotating joints, without penalizing its overall efficiency or even concentration. In this work, two possible optical solutions, combining parabolic-type primaries with second-stage non-imaging optics concentrators for fixed receivers, are presented. These concentrators are designed using the Simultaneous Multiple Surface (SMS) design method and the infinitesimal etendue limit. A performance comparison with a conventional PT in terms of optical efficiency, CAP (Concentration-Acceptance Product) and other performance data are also presented, including an estimate of the total amount of yearly collected energy (kW h/m2 of entrance aperture) for one particular location – Faro (Portugal).
Keywords: Parabolic trough; Fixed receiver; SMS method; Infinitesimal Etendue